Pregnancy rate as an indicator of nutritional status in Rangifer. implications of lactational infertility - Gerhart, K. L.; White, R. G.; Cameron, R. D.; Russell, D. E.; van de Wetering, D. (Rangifer, 1997)
Monitofing pregnancy rates to detect changes in nutrition is best accomplished by sampling lactating females because they will be more responsive to changes in nutrienr availability: nutrition influences pregnancy fate of lactating caribou both through autumn body condition and lactational infertility.